If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(m + -5) = 25 + -5m Reorder the terms: -8(-5 + m) = 25 + -5m (-5 * -8 + m * -8) = 25 + -5m (40 + -8m) = 25 + -5m Solving 40 + -8m = 25 + -5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '5m' to each side of the equation. 40 + -8m + 5m = 25 + -5m + 5m Combine like terms: -8m + 5m = -3m 40 + -3m = 25 + -5m + 5m Combine like terms: -5m + 5m = 0 40 + -3m = 25 + 0 40 + -3m = 25 Add '-40' to each side of the equation. 40 + -40 + -3m = 25 + -40 Combine like terms: 40 + -40 = 0 0 + -3m = 25 + -40 -3m = 25 + -40 Combine like terms: 25 + -40 = -15 -3m = -15 Divide each side by '-3'. m = 5 Simplifying m = 5
| (3)(4)(x)=6 | | 8mx(4m+1)=170 | | -6b(5a-2b)-7(-3ab-4b^2)= | | 45q-32=70q-82 | | a+18=23 | | -2x-6=2-4x-(-x-1) | | (G+8)=2X+H | | 11(x-5)=(x+5) | | -21=2x-9 | | 191-v=89 | | -3(r+6)=-58 | | 3x+2=3(4)+2 | | 4y-4=35-6y | | z^4=28+96i | | 2x-18=3x+8 | | 231=165-y | | x=-12+-3y | | 10G+1=2k+(7X+Y) | | 5r+5-r-5= | | -3.8y=-24 | | 3(3+4)=3x+4 | | 9x^2-26x-35=0 | | 10x=x+81 | | 3x-2(x-9)=2+2x | | 4x+2x-2=12 | | 9x-3+2x-5=2(4x-1) | | 4w-1+9w= | | 5x+17+7x-29=90 | | 5x+5=5y | | 120+-4.5=120 | | 2ax^2-4(a+1)x+4a+1=0 | | 4x^4-4x^3-17x^2-19x-6=0 |